2021
DOI: 10.1097/qad.0000000000002750
|View full text |Cite
|
Sign up to set email alerts
|

All-cause hospitalization according to demographic group in people living with HIV in the current antiretroviral therapy era

Abstract: Objective: We investigated differences in all-cause hospitalization between key demographic groups among people with HIV in the UK in the current antiretroviral therapy (ART) era. Design/Methods: We used data from the Royal Free HIV Cohort study between 2007 and 2018. Individuals were classified into five groups: MSM, Black African men who have sex with women (MSW), MSW of other ethnicity, Black African women and women of other ethnicity. We studied hospitalizations during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 32 publications
1
15
2
Order By: Relevance
“…As reported in a previous study at this London centre [6] , we found that women and heterosexual men of ethnicity other than Black African were at higher risk of hospitalisation compared to MSM. We also found an increased hazard of hospitalisation in individuals over the age of 60, with little variation in risk across the younger age groups.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…As reported in a previous study at this London centre [6] , we found that women and heterosexual men of ethnicity other than Black African were at higher risk of hospitalisation compared to MSM. We also found an increased hazard of hospitalisation in individuals over the age of 60, with little variation in risk across the younger age groups.…”
Section: Discussionsupporting
confidence: 87%
“…We previously reported strong associations between longer time since HIV diagnosis and higher prevalence of physical symptom distress, mental health problems and functional problems, independently of age [34] . Other studies reported some evidence of the opposite association: a negative relationship between time since HIV diagnosis and hospitalisation, [ 7 , 11 ] although a high risk among newly diagnosed individuals may contribute to this [6] . Hepatitis C co-infection has previously been found to predict hospitalisation [ 9 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over time, non-AIDS related causes began to account for an increasing proportion of hospitalisations among PLHIV [4,5]. Previous longitudinal and cross-sectional studies in high-income settings in the cART era have found that demographic factors [6] (including older age [4,[7][8][9][10][11][12][13], female gender [4,9,14], black or minority ethnicity [13,15]) and clinical HIV markers (including low CD4 count [4,7,9,11,13], high viral load [7,9,11,13,16], Hepatitis C or B coinfection [4,9,17] and ART non-adherence [16]) predict hospitalisation among PLHIV. Other studies found evidence that poor mental health was predictive of hospitalisation [8,12,14,18]; findings were less consistent for social [11,14], socioeconomic [10,12,14,19] and lifestyle factors [8,10,12,14,15,…”
Section: Introductionmentioning
confidence: 99%